Sosialisasi Peran Tim Kerja Karyawan Dalam Mendukung Kinerja Usaha Pada UMKM Rumah Jamur - Sri Indrastuti; M. Nur; Armis Armis; Hamdi Agustin (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
The problem of teamwork at the Nando mushroom house business is that the employees are still less compact in the work given, they are more likely to work individually in completing the work, they do not help each other in terms of work, they prefer their own work and finish while other employees not ready in terms of work but they look indifferent without offering help to each other. this will affect employee performance in the future. The purpose of this service is to provide socialization of the role of the employee work team, which is to be able to support business performance at the Nando Mushroom House UMKM in Tenayan Raya Pekanbaru. The result of this service is that the participants understand more about the concept of an Employee Work Team that can support business performance. The mushroom business owner Nando becomes a facilitator to help the team, mediate and resolve conflicts between teams, and interact with the work team.